Effect of different additives, temperature, and immersion time on the inhibition behavior of L-valine for mild steel corrosion in 5% HCl solution. (February 2022) - Mobin, M.; Parveen, M.; Huda; Aslam, R.
Abstract: The effect of addition of different additives – salts, both inorganic (potassium iodide, KI) and organic (sodium benzoate, SB), and non-ionic sugar based surfactant (N-decyl-N′-glucosylethylenediamine, SS) – on the corrosion inhibition behavior of l -valine was studied using potentiodynamic polarization measurement, electrochemical impedance spectroscopy measurement, Fourier transform infra-red spectroscopy, and scanning electron microscopy (SEM)-energy dispersive spectroscopy studies. The effect of temperature (i.e. 30, 40, 50, and 60 °C) and immersion time extending from 1 to 7 days was also explored. The presence of inorganic/organic salts and surfactant induced higher inhibition performance of l -valine to inhibit mild steel corrosion in 5% HCl solution by giving lower corrosion rates. The corrosion rate of mild steel decreased with the presence of additives, and the extent of effect followed the sequence of KI < SB < SS. Lowest values of corrosion rates in the case of SS also reflected a smooth and better morphological surface as shown by SEM. Highlights: Effects of additives on l -valine (Val) anticorrosive action were tested for mild steel. Potassium iodide, sodium benzoate, and a non-ionic surfactant increased Val action. Val alone and Val with additive mixtures acted as mixed-type inhibitors. SEM and FTIR studies confirmed the adsorption of inhibitors on mild steel surface.